IS ADMINISTRATIVE JUSTICE A PROBLEM-SOLVING OF TAX DISPUTE? - Agus P. Priyono; Henry DP Sinaga (Scientia Integritas Utama, 2022)
It is necessary and urgent to construct provisions regarding tax disputes in the tax court. So that the concept (law) of administrative justice is produced as a problem solving of tax disputes. This article uses a normative juridical method with a prescriptive and evaluative line of thought. Indonesia's tax disputes (including central taxes, regional taxes, and customs and excise) are significant. The percentage of decisions that partially and fully grant the disputes submitted by taxpayers is consistently above from 2014 to 2020. The proposed reform of the Tax Court Law, which shows its characteristics as a settlement of tax dispute cases and at the same time as a problem solver, among others, regulates the existence of an appeals conference or hearing and its characteristics before filing a tax dispute. The handling of applicable tax disputes is still limited to resolving dispute cases, not yet reaching a problem-solving of tax disputes. The handling of civil and criminal cases in court and arbitration has adopted the handling of case resolution and problem-solving of arguments. This will only lead to recurring problems in tax disputes, including the filing of appeals and tax claims that remain a lot, the number of beschikking which is granted partially or wholly even though it is based on the same statutory regulations, the incurrence of extra costs, and additional time for the tax-disputinguting parties. Thus, administrative justice can be considered a fair problem solver in resolving tax disputes between taxpayers and the tax authorities.